2014
DOI: 10.3945/ajcn.114.088609
|View full text |Cite
|
Sign up to set email alerts
|

Hypocaloric compared with eucaloric nutritional support and its effect on infection rates in a surgical intensive care unit: a randomized controlled trial

Abstract: Among critically ill surgical patients, caloric provision across a wide acceptable range does not appear to be associated with major outcomes, including infectious complications. The optimum target for caloric provision remains elusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
128
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(136 citation statements)
references
References 31 publications
3
128
2
3
Order By: Relevance
“…The results of the 11 clinical trials in intensive care unit (ICU) patients that have investigated the impact of nutrition support on clinical outcomes within the past 5 y have varied (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). The groups randomly assigned to higher energy intake had improved outcomes in 2 trials (8,9), no difference in 5 (1,(5)(6)(7)10), and worse outcomes in 4 (2-4, 11) than those randomly assigned to a lower intake. The 2 trials that found fewer infections with greater energy intake had problems with unintended imbalanced randomization that led to considerably greater numbers of patients prone to infection in the hypocaloric group (9) or issues regarding outcome reporting (8) that have raised questions about how these results should be interpreted (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the 11 clinical trials in intensive care unit (ICU) patients that have investigated the impact of nutrition support on clinical outcomes within the past 5 y have varied (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). The groups randomly assigned to higher energy intake had improved outcomes in 2 trials (8,9), no difference in 5 (1,(5)(6)(7)10), and worse outcomes in 4 (2-4, 11) than those randomly assigned to a lower intake. The 2 trials that found fewer infections with greater energy intake had problems with unintended imbalanced randomization that led to considerably greater numbers of patients prone to infection in the hypocaloric group (9) or issues regarding outcome reporting (8) that have raised questions about how these results should be interpreted (12).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this long duration, large randomized clinical trials designed to detect the influence of providing enteral nutrition (EN) 8 and/or parenteral nutrition (PN) in this population have been conducted in the past 7 y. The results of the 11 clinical trials in intensive care unit (ICU) patients that have investigated the impact of nutrition support on clinical outcomes within the past 5 y have varied (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). The groups randomly assigned to higher energy intake had improved outcomes in 2 trials (8,9), no difference in 5 (1,(5)(6)(7)10), and worse outcomes in 4 (2-4, 11) than those randomly assigned to a lower intake.…”
Section: Introductionmentioning
confidence: 99%
“…One study found more nosocomial infections in the underfeeding group while there was no significant effect on ICU and hospital mortality and duration of MV (45). Another found no differences regarding infections, ICU and hospital LOS and mortality (47). The last study found no differences in length of MV, hospital or ICU stay and infection but was prematurely interrupted at the first interim analysis with the observation of a statistically significant increase in mortality in the full-feeding group.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, three RCTs compared underfeeding with full-feeding nutritional support in critically ill patients (45)(46)(47). They were excluded from our analysis due to the use of supplementary parenteral nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Diversas pesquisas científicas apontam que a evolução clínica dos pacientes internados depende da adequada ingestão de água, energia e nutrientes (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) .…”
Section: O Cuidado Alimentar E Nutricional No Ambiente Hospitalarunclassified